The Effect of Internal and External Factors to The Number of Visits in Sanitation Clinic of Public Health Center of Poncol Magetan Regency - Djoko Windu P. Irawan; Denok Indraswati; Trimawan Heru Wijono; Bejo Utomo; Suprijandani Suprijandani (Health Notions, 2018)
The Sanitation Clinic program has been introduced and implemented since 2003. But in many places the program does not run well, and is not managed properly, leaving a lot of problems. In some places sanitation clinic activities are conducted without any purposes, and merely administration activity without doing real action. The objectives of the study were to analyze the internal and external factors of the tangible, reliable, responsive, assurance, and emphathy together, and and to find which factor is the most dominantly in influencing the number of sanitation clinic visits. The study was an analytic survey research, it was focused to explain how and why of certain situation. Based on the period of data collection, this study belongs to cross sectional study. Methods of data analysis was using multiple regression method to see whether there is a relationship and the closeness of the relationship of each independent variable to dependent variable, and the relationship between variables in the study. The result of standardized Coefficients Beta from the five dimensions of service quality stated that the assurance dimension (X4) has the largest standardized Coefficients Beta value of -0.007. There was a significant influence jointly between internal and external factors (tangible, reliable, responsive, assurance, and emphathy) on the number of visits. Insurance dimension is the most dominant dimension of the number of visits in Sanitation Clinic in Public Health Center of Poncol, Magetan Regency. Keywords: Internal factors, External factors, Sanitation clinic